2014
DOI: 10.1016/j.aquatox.2014.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Effects of water accommodated fractions of crude oils and diesel on a suite of biomarkers in Atlantic cod (Gadus morhua)

Abstract: The aim of this study was to characterize concentration- and time-dependent responses in juvenile Atlantic cod (Gadus morhua) following exposure for one and three weeks to the water-soluble fraction (WAF) of three weathered oils: Arabian Light crude oil (ALC), North Sea crude oil (NSC) and ship-diesel. The sum of polycyclic aromatic hydrocarbons (PAH) in water was highest after one week of exposure and within environmentally relevant concentrations. PAH metabolites in bile confirmed exposure to and uptake of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 101 publications
6
20
0
Order By: Relevance
“…Dietary exposure to crude oil did not induce effects on the selected molecular endpoints related to vitellogenesis (vtg-β) and steroidogenesis (cyp19α1) in polar cod, which concurs with findings of other experimental studies on the effects of petroleum compounds in fish (Bilbao et al, 2010;Holth et al, 2014). The lack of effects might also be related to the low exposure levels used in the present experiment and to the fact that male and female individuals were differentially represented in each experimental group.…”
Section: Effects Of Crude Oil On Genes Related To Reproductionsupporting
confidence: 91%
“…Dietary exposure to crude oil did not induce effects on the selected molecular endpoints related to vitellogenesis (vtg-β) and steroidogenesis (cyp19α1) in polar cod, which concurs with findings of other experimental studies on the effects of petroleum compounds in fish (Bilbao et al, 2010;Holth et al, 2014). The lack of effects might also be related to the low exposure levels used in the present experiment and to the fact that male and female individuals were differentially represented in each experimental group.…”
Section: Effects Of Crude Oil On Genes Related To Reproductionsupporting
confidence: 91%
“…The oxidative stress tissue profiles observed here match tissue profiles in fish exposed to other oil-related contaminants (e.g. crude oil, diesel52). Importantly, these data also indicate that although salts alter antioxidant enzyme profiles, these effects do not appear to have consequences insofar as oxidative damage.…”
Section: Discussionsupporting
confidence: 60%
“…Because production of cat, gpx, and gst can all be related to H 2 O 2 production and GSH content, elevated gsr synthesis in both WAF and CEWAF dilbit treatments suggested increased turnover and reduced availability of GSH compensating for oxidative stress, as noted in oil-exposed cod larvae (Olsvik et al, 2005). Although elevated levels of gst transcripts and protein activity in combination with similar changes in SOD, CAT, and GPx, are common in fish exposed to related products, such as oil sands process-affected water (OSPW) (He et al, 2012;Gagné et al, 2012), reduced GST activity has been also reported (Holth et al, 2014;Gagné et al, 2011), perhaps due to oxidative inactivation. In the present study, oxidative inactivation in CEWAFexposed medaka would be consistent with high concentrations of TPAH in exposure solutions, high exposure to PAH (also characterized by a strong cyp1a induction), and a high prevalence of BSD.…”
Section: Discussionmentioning
confidence: 87%